2013
DOI: 10.1186/1476-4598-12-84
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of PARM-1 as a new potential oncogene

Abstract: BackgroundThe Graffi murine retrovirus is a powerful tool to find leukemia associated oncogenes. Using DNA microarrays, we recently identified several genes specifically deregulated in T- and B-leukemias induced by this virus.ResultsIn the present study, probsets associated with T-CD8+ leukemias were analyzed and we validated the expression profile of the Parm-1 gene. PARM-1 is a member of the mucin family. We showed that human PARM-1 is an intact secreted protein accumulating predominantly, such as murine PAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
(66 reference statements)
2
18
0
Order By: Relevance
“…3d, e). 95% expressed the transcription factor Krueppel-like factor 2 (Klf2), 93% the cytoskeletal protein Vimentin (Vim) 11 and 62% the golgi/ endosomal-associated gene Prostate androgen-regulated mucinlike protein 1 (Parm1) 12 . In summary, Bsm of cluster I resemble transitional memory B cells 13,14 .…”
Section: Bsm Of Bone Marrow and Spleen Have Distinct Ig Repertoiresmentioning
confidence: 99%
“…3d, e). 95% expressed the transcription factor Krueppel-like factor 2 (Klf2), 93% the cytoskeletal protein Vimentin (Vim) 11 and 62% the golgi/ endosomal-associated gene Prostate androgen-regulated mucinlike protein 1 (Parm1) 12 . In summary, Bsm of cluster I resemble transitional memory B cells 13,14 .…”
Section: Bsm Of Bone Marrow and Spleen Have Distinct Ig Repertoiresmentioning
confidence: 99%
“…In this study, downregulation of PARM1 showed a poor prognostic outcome in PCa patients and its expression was significantly lower in PCa issue compared with benign issue in TCGA and HPA datasets. However, it is also reported that PRAM1 enhanced cell growth in leukemia 53 . The specific function of PARM1 in PCa need to be expounded further.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that PARM1 was able to promote cardiomyogenic differentiation through regulating the BMP / Smad signaling pathway, and the activation of BMP/Smad pathway could inhibit the proliferation and growth of human CRC cells while induce cell apoptosis in CRC and prostate cancer cells . These data collectively suggest that PARM1 may function as a tumor suppressor through regulating the BMP / Smad signaling pathway in CRC although it has reported that PARM1 may function as an oncogene to enhance cell proliferation in leukemia and NIH/3T3 cells . The concept that PARM1 functions as a tumor suppressor are further supported by our current observations that PARM1 expression was significantly lower in tumor tissues compared with the noncancerous tissues and low expression of PARM1 was associated with a poorer outcome in the patients with CRC.…”
Section: Discussionmentioning
confidence: 96%